1993
DOI: 10.1093/ajh/6.4.282
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mass and Geometry in Patients With Established Hypertension and White Coat Hypertension

Abstract: This study was designed to compare the cardiac mass and geometry in white coat hypertensive patients and established hypertensive patients through the prospective comparison of office blood pressure, daytime ambulatory blood pressure, and echocardiographically determined left ventricular mass and cardiac geometry in consecutive patients. We studied 143 patients from general practice in an outpatient hypertension unit. The patients had newly diagnosed mild-to-moderate hypertension prior to the institution of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 0 publications
3
27
1
1
Order By: Relevance
“…And importantly, we have earlier found ABP to be a better predictor of target-organ damage than OBP on cross-sectional data in this study population. 10,11 Longitudinal results have been published by others both in normotensive and in hypertensive populations and they show the same relations as our prospective results. [17][18][19] The high event rate in the WCH group raises the important question of whether there is also a positive relation between WCE and cardiovascular morbidity rate in our population.…”
Section: -Year Follow-up Of Wchsupporting
confidence: 91%
See 2 more Smart Citations
“…And importantly, we have earlier found ABP to be a better predictor of target-organ damage than OBP on cross-sectional data in this study population. 10,11 Longitudinal results have been published by others both in normotensive and in hypertensive populations and they show the same relations as our prospective results. [17][18][19] The high event rate in the WCH group raises the important question of whether there is also a positive relation between WCE and cardiovascular morbidity rate in our population.…”
Section: -Year Follow-up Of Wchsupporting
confidence: 91%
“…[10][11][12]16 In spite of our specific results on the WCH group, this study reveals quite expected overall relations between cardiovascular events and BP data. We found that the event rate was more strongly predicted from ABP than OBP.…”
Section: -Year Follow-up Of Wchcontrasting
confidence: 63%
See 1 more Smart Citation
“…All evaluations were performed in the same batch; hence, the readings were different from the data previously reported. 21 The reason for the blinding procedure was to assure an estimate free from bias, but of course at the cost of lower accuracy which, however, is of less importance due to the relatively high number of subjects. No patient was excluded from analysis because of difficulties in obtaining images, although 55 (11.4%) were considered of minor technical quality.…”
Section: Echocardiographymentioning
confidence: 99%
“…1,2 The prognosis for whitecoat hypertensive subjects is not yet completely clear. [3][4][5][6][7][8][9][10][11][12][13] Some studies have shown that white-coat hypertension is a benign condition, 3,5,6,10,12,13 whereas others have not. 4,[7][8][9]11 We have reported recently that subjects with white-coat hypertension do not show target organ damage and present a lipid profile similar to that in normotensive subjects, 14 suggesting that they could be considered at low cardiovascular risk.…”
mentioning
confidence: 99%